The Blind‐Sight of Statistical Evidence - Vahid, Hamid (Analytic philosophy, 2025)
While it is generally believed that the rationality of belief depends on the adequacy of (individual) evidence on which it is based, it seems that there are certain types of evidence, that is, statistical evidence, which, despite being sufficiently probabilifying, fail to confer justification on the relevant beliefs. In this paper, I will defend a particular solution to this puzzle, namely, the ‘normic support’ view, against some of the objections raised against it. I also appeal to the thesis of phenomenal intentionality to rectify a weakness in the view in question by introducing a necessary condition on when individual evidence can be said to normically support a content. Finally, I offer further reasons for the normic‐support view. It is contended that, unlike cases of individual evidence, which are justification‐conferring, statistical evidence at best provides us with a capacity to reliably guess whether a particular proposition is true, very much like what a blindsight subject can say about the objects in her blind field when contrasted with someone who is perceptually aware of that visual field.